LEGAL PROTECTION OF CANCER PATIENTS’ SOCIAL SECURITY PARTICIPANTS IN TARGETING THERAPY SERVICES IN HOSPITAL - Suanjaya, Made Agus; Sutarno, Sutarno; Zamroni, Mohammad (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
The purpose of this study to analyse laws and regulations as legal protection for social security participants in targeting therapy services in hospitals and to analyse the responsibility of the hospital for targeting therapy services. Legal protection for cancer patients participating in social security in targeting therapy services in hospitals in accordance with what is regulated in the 1945 Constitution, then Law Number 29 of 2004 concerning Medical Practice; Law of the Republic of Indonesia Number 36 of 2009 concerning Health, which shows that the state present in providing protection and legal protection to its people. So in practice in the field, both hospitals and medical personnel must stick to this rule so that cancer patients participating in social security receive optimal service in accordance with the latest scientific principles of medicine without violating applicable laws so as to create harmony between optimal patient treatment and applicable law. Hospital responsibility for targeting therapy services is crucial/important where hospitals have criminal responsibility regulated in the Criminal Code, civil liability related to default and unlawful acts as stated in the Civil Code and also administrative responsibility which is regulated in the rules medical.